Pengaruh Endorser terhadap Purchase Intention dengan Perceived Value dan Perceived Usefulness sebagai Variabel Mediasi (Studi Pada Viewer Food Vlogger of YouTube Channel) - Dyajeng Puteri Woro Subagio; Dwita Laksmita Rachmawati (University of Merdeka Malang, 2020)
The main objective of this study is to investigate, describe and analyze the direct and indirect effect of endorsing, perceived value, and perceived usefulness on purchase intention. Statistical population of the present study is all viewer five food vloggers with the most subscribers on YouTube channel in Indonesia. This study uses questionnaires as the research instrument with 200 respondents as the sample. Sampling technique is purposive sampling. This study uses Partial Least Square (PLS) to analyze the data. The result shows there is a significant direct effect of endorser credibility on perceived value and perceived usefulness. In addition, perceived value and perceived usefulness have a significant influence on purchase intention. This study also confirms that perceived value and perceived usefulness mediates the influence of endorser credibility on purchase intention. However, the other result shows that there is no significant relationship between endorser credibility of food vlogger on purchase intention. Distance and price are the main reasons customer has no purchase intention of food product that has been reviewed by endorsers. https://doi.org/10.26905/jmdk.v8i1.3997